Model Pembelajaran PROTAGET untuk Meningkatkan Motivasi Belajar dan Keterampilan Berpikir Kritis Siswa Kelas V pada Pembelajaran Matematika - Mery Arrizqa Ulya; Maimunah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze the implementation of the PROTAGET learning model in enhancing the learning motivation and critical thinking skills of fifth-grade students during mathematics lessons. The study employed a Classroom Action Research approach based on the Kemmis and McTaggart model, comprising four stages: planning, action implementation, observation, and reflection. The research was conducted over four sessions with 33 fifth-grade students at SDN Kuin Cerucuk 3, Banjarmasin. Data were collected through observations and tests covering teacher activity, student activity, learning motivation, critical thinking skills, collaboration skills, and learning outcomes. The data were analyzed using both qualitative and quantitative descriptive methods. The results indicate that all observed aspects showed gradual improvement. Teacher activity increased from 82.50% to 92.50%, student activity from 69.70% to 100%, learning motivation from 48.50% to 100%, critical thinking skills from 39.40% to 100%, and collaboration skills from 45.50% to 100%; additionally, the class mastery rate for learning outcomes rose from 57.58% to 100%. These findings demonstrate that the PROTAGET learning model fosters active, collaborative, and student-centered mathematics instruction, making it effective in boosting students' learning motivation and critical thinking skills. Consequently, the PROTAGET learning model serves as a viable alternative for innovative mathematics instruction in primary schools.